Preparation of ferrimagnetic BF based silicate glass system - Wilaiwan Leenakul (2018)
© 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved. Magnetic bioglass-ceramics have been introduced recently for hyperthermia treatment of bone cancer. Ferrimagnetic bioactive glass was synthesized by doping BaFe < inf > 12 < /inf > O < inf > 19 < /inf > ; (BF) into SiO < inf > 2 < /inf > -CaO-Na < inf > 2 < /inf > O-P < inf > 2 < /inf > O < inf > 5 < /inf > glass system using the modified solid-state sintering method. The effects of various sintering temperatures (800-900 °C) and BF contents on physical properties, bioactivity and magnetic properties of samples were investigated. The results confirmed the occurrence of Na < inf > 6 < /inf > Ca < inf > 3 < /inf > Si < inf > 6 < /inf > O < inf > 18 < /inf > and BaFe < inf > 12 < /inf > O < inf > 19 < /inf > phases in all prepared glass ceramics. It was found that BF addition and sintering temperature caused an alteration in magnetic behavior from hard to soft magnetic. The magnetic properties were related to the microstructure, including porosity and density of samples. The bioactivity of the BF glass ceramics improved with increasing BF content as evident by the formation of bone-like apatite layers on the surface of all glass ceramics after soaking in SBF for 7 days. The results support the use of these bioactive glass ceramics for hyperthermia treatment within the human body.